Clinical vignettes for the USMLE Step 2 CK : Pre Test self-assessment and review. - McGraw-Hill Companies (New York : McGraw-Hill, Medical Pub. Division, 2006)
Clinical Vignettes for the USMLE Step 2 CK is a compilation of the best questions from eight McGraw-Hill PreTest clinical review books and provides you with the perfect vehicle for assessing your knowledge before taking the USMLE Step 2 CK exam. The book is a comprised of 368 clinical vignettes divided into eight blocks of 46 questions and provides one complete board exam to simulate the exam-day experience. This is the comprehensive practice exam to take before you take the test.--Publisher's website.
Preface -- Questions -- Block 1 -- Block 2 -- Block 3 -- Block 4 -- Block 5 -- Block 6 -- Block 7 -- Block 8 -- Answers -- Block 1 -- Block 2 -- Block 3 -- Block 4 -- Block 5 -- Block 6 -- Block 7 -- Block 8 -- Bibliography.
Rev. ed. of: Pre Test clinical vignettes for the USMLE step 2. 3rd ed. 2003.
Includes bibliographical references.
Keywords: Clinical Medicine; Medicine; Medicine